ANTIBACTERIAL ACTIVITY OF ETHNOMEDICINALLY USED MEDICINAL PLANTS BY THE TRADITIONAL HEALERS OF THIRUVALLUR DISTRICT, TAMILNADU, INDIA - Sakthi, Siva; M, Vijayalakshmi; S, Sankaranarayanan; Bama, P; J, Ramachandran; Deecaraman, M (Innovare Journal of Life Sciences, 2013)
ABSTRACT The objective of this study was to collect information about medicinal plants and their uses, by the knowledge obtained from the traditional healers in Thiruvallur district, Tamilnadu, India. It also determines antimicrobial activity of ten different plants selected based on spearman rank correlation. The traditional healers of Thiruvallur district use different species of medicinal plants belonging to different families for the treatment of various diseases. Commonly maximum number of species has been used for fever followed by skin infection, wound healing and antiseptic. Herbs were found to be the most used plants followed by climbers and shrubs. The spearman rank correlation was used to analayse the knowledge about medicinal plants. Antibacterial activity of ten medicinal plants (Justicia gendarussa, Tephrosia purpurea, Phyllanthus maderaspatensis, Elephantopus scaber, Trichodesma indicum, Rhinacanthus nasatus, Sida cordifolia, Lepidagathis cristata, Evolvulus nummularius and Aerva lanata)Â was determined by measuring the diameter of zone of inhibition that is the mean of triplicates+standard deviation of three replicates. The traditional healers in Thiruvallur district possess rich ethno-botanical knowledge. This study on medicinal plants will attract ethano botanist, phytochemist and pharmacologist in identifying novel antibacterial compounds. Keywords: Antibacterial; Medicinal plants; Traditional Medicine